Simulation and Role Play Techniques to Increase ESP Students’ English Speaking Skill - Sri Wahyuni (LINGUA LITERA : journal of english linguistics and literature, 2015)
This paper discusses about the effectiveness of simulation and role play techniques on students’ English speaking skill. This was based on some problems faced by students either in the process or production. To find out the effectiveness, simulation was treated in experimental group with 22 students, and role play technique was treated in control group with 27 students. These two group treatments were selected randomly by using cluster sampling from the population, the third year students of medical faculty of Baiturrahmmah University Padang which were classified into eight classes. This research was conducted for 8 meetings. After 8 meetings, the data were collected by the posttests and scored by two reviewers. Then the students’ average scores from the two reviewers in the experimental group were compared to the students’ average scores from the two reviewers in control group by t-test. The aim was to test the researchhypothesis. From the calculation of t-test, t-observed yielded 3.89. The total case degree of freedom was 45 ((22-1) + (25-1)). T-table at the 0.05 p-leveland 40 degree of freedom (the closest df) results in a figure of 2.02. This calculation reveals that t-observed could exceed the t-table. It means that theresearch hypothesis was statistically accepted, and null hypothesis was rejected. Therefore, the simulation technique gives better effect on students’English speaking skill than the role play technique.